Evaluating the Impact of Software Testing Education through the Flipped Classroom Model in Deriving Test Requirements - Paschoal, Leo Natan; Oliveira, Myke M.; Melo, Silvana M.; Barbosa, Ellen F.; Souza, Simone R. S. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Recent studies have shown that software testing professionals, for the most part, conduct testing activity in a non-systematic way in software projects developed in the industry. In this sense, with the understanding that it is necessary to educate professionals capable of performing the test activity in a systematic way, the community of Software Engineering educators has paid attention to teaching test criteria. In particular, studies have been carried out in the context of different pedagogical models to recognize the models that manage to promote effective learning. In this perspective, research is being conducted on the flipped classroom pedagogical model. Although there are already experimental studies on this model, they did not investigate whether the student studying with the flipped classroom model can apply the test criteria effectively, deriving the test requirements satisfactorily. Our study emerges intending to analyze these issues. The study is configured using an experimental process that compares the test requirements derived by students who studied with the flipped classroom model, with test requirements derived by students who studied with the traditional teaching model. From the observed dependent variables (efficiency, efficacy, and effectiveness), it is possible to notice that students who study with the flipped classroom model derive test requirements that satisfy the equivalence partitioning criterion of the software under test with greater effectiveness compared to students who study with the traditional teaching model.